Comparative Analysis of WUSCHEL-Related Homeobox Genes Revealed Their Parent-of-Origin and Cell Type-Specific Expression Pattern During Early Embryogenesis in Tobacco - Zhou, Xuemei; Guo, Yingying; Zhao, Peng; Sun, Meng-xiang (Frontiers in Plant Science, 2018)
WUSCHEL-related homeobox (WOX) gene is a plant-specific clade of homeobox transcription factors. Increasing evidences reveal that WOXs play critical roles in early embryogenesis, which involves zygote development, initiation of zygote division, and apical or basal cell lineage establishment. However, how WOXs regulate these developmental events remains largely unknown, and even detailed expression pattern in gametes and early proembryos is not yet available. Here, thirteen WOX family genes were identified in Nicotiana tabacum genome. Comparative analysis of 13 WOX family genes with their homologs in Arabidopsis thaliana reveals relatively conserved expression pattern of WUS and WOX5 in shoot/root apical meristem. Whereas variations were also found, e.g. lacking homolog of WOX8 (a marker for suspensor cell) in tobacco genome and the expression of WOX2/WOX9 in both apical cell and basal cell. Transient transcriptional activity analysis revealed that WOXs in WUS clade have repressive activities for their target’s transcription, whereas WOXs in ancient and intermediate clade have activation activities, giving a molecular basis for the phylogenetic classification of tobacco WOXs into three major clades. Expression pattern analysis revealed that some WOXs (e.g. WOX 13a) expressed in both male and female gametes and some WOXs (e.g. WOX 11 and WOX 13b) displayed the characteristics of parent-of-origin genes. Interestingly, some WOXs (e.g. WOX2 and WOX9), which are essential for early embryo patterning, were de novo transcribed in zygote, indicating relevant mechanism for embryo pattern formation is only established in zygote right after fertilization and not carried in by gametes. We also found that most WOXs displayed a stage-specific and cell type-specific expression pattern. Taken together, this work provides a detailed landscape of WOXs in tobacco during fertilization and early embryogenesis, which will facilitate the understanding of their specific roles in these critical developmental processes of embryogenesis.